(untitled) (Revista horizonte, 2012)
The present review examines possible regulatory factors of the glycolysis in the human skeletal muscle. The glycolysis is regulated for multiple factors among which is present the physical exercise (intensity, rest interval, etc.). There exist negative feedbacks in which the glycolysis and the oxidation (in cardiac muscle and skeletal muscle) process interact. Depending on the exercise type (continuous or intermittent), the flux of glycolysis would varied. Furthermore, with the practice of exercise, the expression of enzymes than are involved directly in the glycolysis would change. Therefore, by expose individuals to different types of exercise, it would be expected a set of physiological adaptations, focused in the energy production and utilization; this adaptations would reduce the stress of exercise.